2016
DOI: 10.1002/2016ja023389
|View full text |Cite
|
Sign up to set email alerts
|

Poynting vector and wave vector directions of equatorial chorus

Abstract: We present new results on wave vectors and Poynting vectors of chorus rising and falling tones on the basis of 6 years of THEMIS (Time History of Events and Macroscale Interactions during Substorms) observations. The majority of wave vectors is closely aligned with the direction of the ambient magnetic field (B0). Oblique wave vectors are confined to the magnetic meridional plane, pointing away from Earth. Poynting vectors are found to be almost parallel to B0. We show, for the first time, that slightly obliqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 71 publications
3
30
1
Order By: Relevance
“…The chorus is primarily field aligned, with wave normal angles generally <30 ∘ , but occasionally reaching more oblique angles in weaker parts of the elements, consistent with previous results of Santolík et al (2014). Not shown, wave azimuthal angles mostly point away from Earth (meridional plane), consistent with typical chorus observations (Taubenschuss et al, 2016).…”
Section: Properties Of Larger Chorus and Microburst Active Regionsupporting
confidence: 90%
“…The chorus is primarily field aligned, with wave normal angles generally <30 ∘ , but occasionally reaching more oblique angles in weaker parts of the elements, consistent with previous results of Santolík et al (2014). Not shown, wave azimuthal angles mostly point away from Earth (meridional plane), consistent with typical chorus observations (Taubenschuss et al, 2016).…”
Section: Properties Of Larger Chorus and Microburst Active Regionsupporting
confidence: 90%
“…In the cases of whistler mode chorus waves which are seen in the magnetosphere, frequencies of the whistler mode waves often show frequency rising (rising tone) (e.g., Kurita et al, 2012; Santolík et al, 2003; Taubenschuss et al, 2016), while there is no clear tendency of frequency variation (rising tone or falling tone) in the present cases (Figure 9c and other events). Nakamura et al (2016) showed that even fluctuations of frequencies can cause nonlinear growth of the waves (Omura et al, 2008) from the observations of whistler mode waves called plasmaspheric hiss.…”
Section: Discussionmentioning
confidence: 50%
“…In the cases in the magnetosphere, the minimum‐ B along B corresponds to the magnetic equator. Simulation studies (e.g., Hikishima et al, 2009; Katoh & Omura, 2007, 2011, 2013; Ke et al, 2017; Kuzichev et al, 2019; Lu et al, 2019) and observations of Poynting flux direction by various spacecraft around the magnetic equator (e.g., Agapitov et al, 2013; Le Contel et al, 2009; LeDocq et al, 1998; Li et al, 2013; Nagano et al, 1996; Parrot et al, 2003; Santolík et al, 2003; Santolík et al, 2005; Taubenschuss et al, 2016; Teng et al, 2018) indicate that wave generation occurs around the magnetic equator and the waves are radiated away from the equator in the parallel and antiparallel directions with respect to B . Thus, reversals of the field‐aligned component of Poynting fluxes are regarded as the sign of the passage of a wave source region.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that chorus waves can be reflected within the magnetosphere, likely when the waves encounter boundaries with very sharp density gradients. Taubenschuss et al () revisited chorus statistics from the THEMIS mission, and they found Poynting vectors that were strongly field aligned and that the most oblique wave normal vectors were confined to the magnetic equatorial plane and had azimuthal angles (in the plane perpendicular to B 0 , the background magnetic field) that pointed away from Earth. They also found that for the majority of lower band chorus waves, the Poynting and wave normal vectors were coplanar with B 0 , indicating a dispersion relation consistent with that of cold plasma theory, and the wave normal vectors became more field aligned with increased latitude.…”
Section: Introductionmentioning
confidence: 99%